The protective role of daidzein in intestinal health of turbot (Scophthalmus maximus L.) fed soybean meal-based diets - Guijuan Yu (Nature Portfolio, 2021)
Abstract Soybean meal-induced enteropathy (SBMIE) is prevalent in aquaculture. The aim of this study is to evaluate the role of daidzein on SBMIE of juvenile turbot (Scophthalmus maximus L.) by feeding with fish meal diet (FM), soybean meal diet (SBM, 40% fish meal protein in FM replaced by soybean meal protein) and daidzein diet (DAID, 40 mg/kg daidzein supplemented to SBM) for 12 weeks. We found that daidzein supplementation elevated the gene expression of anti-inflammatory cytokine TGF-β, decreased gene expression of pro-inflammatory cytokines TNF-α and signal molecules p38, JNK and NF-κB. SBM up-regulated the genes expression related to oxidative stress and apoptosis, but dietary daidzein restored it to the similar level with that in FM group. Moreover, dietary daidzein up-regulated gene expression of tight junction protein, and modified the intestinal microbial profiles with boosted relative abundance of phylum Proteobacteria and Deinococcus–Thermus, genera Sphingomonas and Thermus, species Lactococcus lactis, and decreased abundance of some potential pathogenic bacteria. In conclusion, dietary daidzein could ameliorate SBM-induced intestinal inflammatory response, oxidative stress, mucosal barrier injury and microbiota community disorder of turbot. Moreover, p38, JNK and NF-κB signaling might be involved in the anti-inflammatory process of daidzein, and daidzein itself might act as an antioxidant to resist SBM-induced oxidative damage.